Mediation analysis of the association between use of NRT for smoking reduction and attempts to stop smoking. - Beard, E; Aveyard, P; McNeill, A; Michie, S; Fidler, J; Brown, J; West, R (Routledge, 2012)
OBJECTIVES: Use of nicotine replacement therapy (NRT) for smoking reduction (SR) is linked to higher quit attempt rates than SR without NRT. This study aimed to assess the possible mediating roles of confidence in ability to quit, enjoyment of smoking and motivation to quit in this association. DESIGN: Cross-sectional survey. MAIN OUTCOME MEASURES: Smokers were asked if they were currently attempting SR, and if they were, whether they were using NRT. Motivation to stop, enjoyment of smoking, confidence in ability to stop, and previous quit attempts, were also assessed. RESULTS: There was no evidence that confidence in ability to quit or enjoyment of smoking mediated the association between the use of NRT for SR and attempts to quit. Only motivation to stop partially mediated between the use of NRT for SR and attempts to stop (indirect effect: odds ratio 1.08, p < 0.001). CONCLUSION: Although this study is limited by its cross-sectional design, the findings point towards the possibility that the use of NRT to aid SR may promote attempts to stop through increasing motivation to quit but not by increasing confidence or by reducing enjoyment of smoking. Longitudinal studies are required to draw firmer conclusions about the possible mediating effects of motivation to quit.